ANALISIS KEBUTUHAN LAHAN DAN BANGUNAN UNTUK PEMENUHAN STANDAR NASIONAL PENDIDIKAN SARANA PRASARANA - Sri Mulyaningsih (Jurnal Tata Kelola Pendidikan, 2021)
Facilities and infrastructure are very important support for the implementation of quality education. Building conditions, land area, classrooms, laboratories and libraries for example can affect the teaching and learning process. This will result in the competency standards of graduates later. This study aims to determine the amount of costs required to meet the standard of facilities and infrastructure, especially for the addition of land area and building area for junior high schools in Batununggal District. The research method used is qualitative research methods with 3 research objects, with the conclusion (1) the cost required at SMPN 4 Bandung for standard compliance, which is Rp. 11,791,352,456.00 (2) The cost required at SMPN 20 Bandung for standard compliance , namely Rp. 3,058,495,368.00 (3) The cost required at SMPN 31 Bandung for standard compliance is Rp. 2,209,174,986.00. To be able to meet the standards of educational facilities and infrastructure, schools can collaborate with the community so that they can use learning facilities that cannot be fulfilled by the school.